Analisis Kestabilan Model Matematika Dinamika Penyebaran Rumor melalui Media Sosial dan Verbal - Fauziah, Helena; Winanda, Rara Sandhy (Journal of Mathematics UNP, 2024)
Rumor, unverified information, propagate swiftly through word of mouth and social media. This research will discuss a mathematical model of the dynamics of rumor spreading through social media and verbal with four compartments, namely I, M, G and R. This is referred to a basic research (theoretical) using descriptive method. The results of this research indicate that the rumor-free equilibrium point is asymptotically stable if it satisfies the conditions, meaning that no rumor spreads in the population; the rumor-endemic equilibrium point through verbal is asymptotically stable if it satisfies the conditions, meaning that rumors spread but only through verbal in the population; and the rumor-endemic equilibrium point through media is asymptotically stable if it satisfies the conditions, meaning that rumors spread but only through media in the population.